ChemInform Abstract: Antimicrobial and anti‐Nociceptive Profile of Some 4‐(3‐Methyl‐1‐phenyl‐1H‐pyrazol‐4‐yl)‐1‐phenylazetidin‐2‐ones. Issue 28 (July 2015) - Sen, Sandip; Easwari, T. S.; De, Biplab
Abstract A new series of the title compounds (IX) is prepared via intermolecular cyclization of Schiff bases (VII) and chloro acetyl chloride in the presence of the base catalyst triethylamine.